Metabolic costs of aggressive behaviour in the siamese fighting fish, Betta splendens - Castro, Nídia (2012)
Aggressive conflicts between males are often resolved by means of multiple ritualized agonistic displays without damaging escalation. Apparently, in such cases by using those displays opponents exchange important motivational and physical information on which they base a decision to stay or leave the interaction. In the Siamese fighting fish, the time spent spreading the dorsal fin and erecting the gill coverts predicts who will be the winner or loser of the interaction. Two experiments were carried out to study whether display performance might be costly. First, oxygen consumption was measured during mirror-image stimulation. This experiment showed that oxygen consumption was positively correlated with gill cover erection and dorsal fin spread. In the second experiment, a fight between two opponents was simulated and the oxygen consumption of the expected winner and loser was compared. Metabolic rates were not different between winners and losers before and during the fight, but winners showed higher oxygen consumption in the night after the fight. These results are in accordance with costs of display performance and with longlasting physiological consequences of winning or losing a fight.